Valoración del patrimonio cultural material como recurso turístico en la ciudad creativa: caso de estudio ciudad de Portoviejo - Pionce Tapia, Jhon Jairo (2024)
The objective of this research is to determine the valuation of the material cultural heritage as a tourist resource in the creative city of Portoviejo. For the realization of the work of curricular integration it was necessary the fulfillment of the methodology composed of three phases; In the first phase a diagnosis was made where, thanks to the characterization of the study area, it was indicated that the city has legal instruments that contribute to the management of cultural resources; subsequently, the main heritages of the city were identified yielding a total of forty. In the second phase, an analysis of tourism supply and demand was made, for which interviews were conducted emphasizing that the Archaeological Museum of Jaboncillo is a place of interest for tourists visiting the territory, so it is important to safeguard its heritage identity in order to protect the site using strategies proposed. Through an analysis, ideas for the valuation of the city's cultural heritage were developed. Finally, the third phase was focused on the elaboration of action strategies, where the experts played an important role in the validation of those strategies, which were proposed through three steps: execution of the INPC heritage card, valuation of the cultural resources with the aforementioned tool, and the proposal of strategies approved by the cultural specialists. In this way, the integrated approach of the research offers direct guidelines that promote the effective protection and promotion of the tangible cultural heritage of the creative city of Portoviejo.